2016
DOI: 10.1038/nrdp.2015.86
|View full text |Cite
|
Sign up to set email alerts
|

Patent foramen ovale

Abstract: Patent foramen ovale (PFO) is the most common congenital heart abnormality of fetal origin and is present in approximately ∼25% of the worldwide adult population. PFO is the consequence of failed closure of the foramen ovale, a normal structure that exists in the fetus to direct blood flow directly from the right to the left atrium, bypassing the pulmonary circulation. PFO has historically been associated with an increased risk of stroke, the mechanism of which has been attributed to the paradoxical embolism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(126 citation statements)
references
References 152 publications
1
90
2
7
Order By: Relevance
“…Although many authors have confirmed the statistical association between PFO and unexplained neurological events especially in young patients, the causality has not been conclusively established. This is an area of clinical uncertainty and ongoing debate [58].…”
Section: Patent Foramen Ovalementioning
confidence: 99%
“…Although many authors have confirmed the statistical association between PFO and unexplained neurological events especially in young patients, the causality has not been conclusively established. This is an area of clinical uncertainty and ongoing debate [58].…”
Section: Patent Foramen Ovalementioning
confidence: 99%
“…() and Homma et al . (). In brief, shunts in the mammalian foetus (and, with a few small differences, in the avian embryo) occur through both intracardiac and external vascular mechanisms and structures.…”
Section: Cardiovascular Shunts In Ectothermic Vertebrates: Theories mentioning
confidence: 99%
“…The role of central vascular shunts in developing mammals has been considered in great detail, not only with regard to the basic biology of shunting in endotherms, but also because of their importance in human development and the management of pathologies during foetal development. It is not our intention to review here this material, largely of a clinical nature -we instead refer the reader to reviews in Achiron & Kivilevitch (2016), Anilkumar (2013), Araujo Junior et al (2016, Dzialowski et al (2011) andHomma et al (2016). In brief, shunts in the mammalian foetus (and, with a few small differences, in the avian embryo) occur through both intracardiac and external vascular mechanisms and structures.…”
Section: (7) Developmental Context (A) Endothermsmentioning
confidence: 99%
“…1). In the course of a venous-arterial shunt, paradoxical embolism may occur, where venous emboli or thrombi may pass from venous to arterial circulation causing ischaemic strokes [3,4,5,6]. While diving, the PFO may be the route for gas bubbles that appear during normal decompression or in the course of the decompression sickness, which may then penetrate arterial vessels.…”
Section: Introductionmentioning
confidence: 99%